Ecotoxicological hazard and risk assessment of endocrine active substances. (18th January 2017) - Leopold, Annegaaike; Roberts, Mike; Matthiessen, Peter
ABSTRACT: This collection of papers provides state‐of‐the‐art science on a complex topic that has been challenging for scientists and regulators for a long time. The papers emanated from the Society of Environmental Toxicology and Chemistry (SETAC) Pellston Workshop ® Environmental Hazard and Risk Assessment Approaches for Endocrine‐Active Substances (EHRA). Forty‐eight international experts met in early February 2016 to discuss whether the environmental risks posed by endocrine‐disrupting substances (EDS) can be reliably assessed. The primary conclusion of the workshop was that if data on environmental exposure, effects on sensitive species and life‐stages, delayed effects, and effects at low concentrations are robust, initiating environmental risk assessment of EDS is scientifically sound and reliable. Integr Environ Assess Manag 2017;13:264–266. © 2016 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals, Inc. on behalf of Society of Environmental Toxicology & Chemistry (SETAC) Key Points: A SETAC Pellston Workshop "Environmental Hazard and Risk Assessment Approaches for Endocrine‐Active Substances (EHRA)" was held in February 2016 to discuss whether the environmental risks posed by endocrine‐disrupting substances (EDS) can be reliably assessed. The workshop and resulting papers address a clear need for objective advice, based on the current level of scientific understanding, to allow regulators and policy makers to make comprehensive, science‐based decisions on the risk and hazard assessment of endocrine‐disrupting substances.